From concept to consumption: the role of product design in shaping consumer preferences and buying decisions - Abdul Gafar, Muhammad Hanif; Mohd Ali, Nor Amira (International Journal of Accounting, Finance and Business, 2025)
In an increasingly competitive market, product design plays a crucial role in shaping consumer preferences and influencing purchasing decisions. Despite its significance, limited research has comprehensively examined how various design elements such as aesthetics, functionality, and sustainability have impact on the consumer behavior across different industries. This study aims to explore the intersection of product design and consumer behavior, focusing on emerging themes such as sustainable fashion consumption, neuromarketing, digital marketing, product customization, and sustainable product design. By analyzing existing literature and key theoretical frameworks, this study identifies how these themes contribute to evolving consumer preferences and market trends. A qualitative approach was adopted, utilizing a systematic review of peer-reviewed articles and emerging research trends to synthesize insights from multiple disciplines, including consumer psychology, design studies, and marketing science. The findings reveal that sustainable consumer behavior in fashion remains a consistent theme, with green marketing and corporate social responsibility initiatives significantly enhancing brand loyalty. Additionally, neuromarketing techniques demonstrate the power of emotional and sensory branding in influencing consumer decision-making. Due to the rising trends, such as digital and sustainable fashion marketing and product customization, highlight the increasing importance of personalized and transparent consumer experiences. Theoritically, the study’s implications contributes to consumer behavior literature by reinforcing psychological and behavioral theories related to product design but practically, it provides businesses with actionable insights for developing sustainable, consumer-centric design strategies. However, further empirical research is needed to validate these findings through experimental and cross-cultural studies. Future research should also explore the role of AI and virtual reality in enhancing digital product experiences.